2000
DOI: 10.1111/j.1754-4505.2000.tb01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital‐based dental care for persons with disabilities: a study of patient selection criteria

Abstract: The objective of this investigation was to generate a medical and dental profile of patients attending the Mount Sinai Hospital Dental Program for Persons with Disabilities, to determine if certain selected criteria could identify patients likely to require dental care in that setting. The need for dental care under general anesthesia was used as the prime indicator that care should be provided in a hospital setting. A retrospective review of all the charts of the patients enrolled in this hospital program was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 13 publications
0
28
1
4
Order By: Relevance
“…Studies have shown that people with disability, regardless of the type of disability, presented with a consistently poorer state of oral hygiene, with various levels of periodontal diseases, higher level of untreated dental caries and greater need for extractions than their normal peers (4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that people with disability, regardless of the type of disability, presented with a consistently poorer state of oral hygiene, with various levels of periodontal diseases, higher level of untreated dental caries and greater need for extractions than their normal peers (4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is important to take into account the type of disability, age and demographic situation of each population studied. 10 The aim of this investigation was to determine and compare the type, number of procedures and working time length of dental treatment provided under dental general anesthesia in healthy and in medically compromised/developmentally disabled (MCDD) children.…”
Section: Dental Treatment Under General Anesthesia In Healthy and Medmentioning
confidence: 99%
“…Nestas condições os pacientes podem sofrer diminuição da oxigenação sanguínea ou aspirar conteúdos gástricos 2,3 . Em tratamentos odontológicos, grande parte dos pacientes apresentam medo e ansiedade 3,[5][6][7] , sentimentos que podem ser exacerbados por procedimentos que geram dor 3,7,8 . Embora muitas técnicas de condicionamento de comportamento possam ser empregadas, existe uma parcela de pacientes ansiosos ou apreensivos, com deficiências físicas e/ou mentais, que necessitam de métodos adjuvantes para viabilizar o tratamento odontológico 1,3,7 .…”
Section: Introductionunclassified
“…Em tratamentos odontológicos, grande parte dos pacientes apresentam medo e ansiedade 3,[5][6][7] , sentimentos que podem ser exacerbados por procedimentos que geram dor 3,7,8 . Embora muitas técnicas de condicionamento de comportamento possam ser empregadas, existe uma parcela de pacientes ansiosos ou apreensivos, com deficiências físicas e/ou mentais, que necessitam de métodos adjuvantes para viabilizar o tratamento odontológico 1,3,7 . Na maioria dos casos, a sedação consciente é o procedimento de escolha e, para este fim, diversos tipos de drogas podem ser utilizadas, tais como o óxido nitroso 6,9,10 , o hidrato de cloral 11,12 .…”
Section: Introductionunclassified